Pharmacy Technician Workload and Workforce Requirements at MOH Hospitals during Ten years Mass Gathering Hajj (2006-2015) in Makah Region, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the Pharmacy technician services workload analysis and human resources requirements at Ministry of Health Hospitals during mass gathering Hajj ten years (2007-2016), Saudi Arabia. Methods: It is a retrospective of ten years (2007-2015) of hospital Pharmacy technician workload during mass gathering Hajj period. The duration of workload collection was 15 days. The Pharmacy technician prepares the medications and pharmaceutical to all patients either Pilgrim or not Pilgrim at Makah region. It included Mona holy places hospitals; Arafa holy places hospitals, and Makah city. The workforce requirements calculated based on MOH workforce standards per bed and the workload drives as central Pharmacy technician services, patient specific Pharmacy technician activities, and Pharmacy technician administration specific pharmacy activities. Results: The total number of Pilgrims (1,952,817-3,161,573) with average of (2,445,208). The total number of prescriptions (99,886-257,545) with average (180,120), it represented (5.11-12.07%) with average (7.86%) of all pilgrims. The average number of pharmacy technician calculated per hospital was (17.74 FTE), while the mean number pharmacy technician needed based on workload for all services was (110.95FTE) per hospital in all Makka region. It is (6.12 fold) more incremental than MOH pharmacy technician workforce standards per bed. Conclusion: Despite the clinical pharmacy technician’s activities missed with emphasis on patient-specific clinical pharmacy technician and administrative pharmacy technician performances. There is a high demand for pharmacy technician workforce during mass gathering Hajj period in Makah Region, Saudi Arabia.
Keywords: Pharmacy technician; Workload; Workforces; Mass Gathering; Hajj; Makka; Ministry of Health; Saudi Arabia